A Qualitative Study of Barriers to Physicians\' Participation in Accreditation Program in Public Hospitals - Seyyed Morteza Mojtabaeian; Fatemeh Monfared (Tehran University of Medical Sciences, 2022)
Background and Aim: The participation of doctors and clinical leadership in organizational strategies to improve quality performance is a necessary precondition for providing safe and high-quality care, and since improving the quality of health care services and increasing the participation of doctors in accreditation is very necessary, the present study was conducted with the aim of explaining the obstacles of doctors' participation in the accreditation programs of Iranian hospitals with a qualitative approach. Materials and Methods: In this study, using the snowball sampling method, interviews were conducted with 11 managers, 9 doctors and 8 officials and experts in the field of quality management (a total of 28 people) in the field of hospital accreditation. Interviewees were selected through purposive snowball sampling. To collect data, unstructured and semi-structured in-depth interviews were conducted. The obtained data were analyzed using the conceptual framework method in ATLAS.ti. Results: The results of this research extracted 3 main issues including cultural, organizational and behavioral factors. Also, this research found 12 sub-themes and 57 items. Subtopics in the cultural area were motivation, patient demand, mutual trust, and evaluation system. The organizational field included seven sub-topics, including high workload, understanding the role of the quality management unit, unrealistic accreditation, the nature of accreditation, empowering doctors in the field of quality, effective communication, and limited resources. Subthemes in the behavioural dimension were role ambiguity and uncertainty about how to participate in the accreditation program. The most repeated challenges in the interviews were expressed in the field of effective communication and the least in the field of role ambiguity. Conclusion: Physicians' participation in accreditation programs can be increased through culture building and proper training in accreditation activities in the medical community. By revising the categories of activities performed in the hospital by doctors and including a specific time to perform activities to improve quality and accreditation and create a balance between the quantity and quality of services provided in the hospital, it is possible to increase the participation of doctors in the accreditation program.